’56-os magyar menekültek Szudánban - Udvarvölgyi, Zsolt András (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
In my paper I briefly summarize the short history of the entry of Hungarian refugees into Africa in 1956, then I look at Sudan and briefly outline the main cornerstones of the establishment of Sudanese-Hungarian diplomatic relations. Next, I will describe in detail the reports of the Hungarian legation in Khartoum, dated 1956-1959, about the three Hungarian refugees emmigrated to Sudan. It is a remarkable and hitherto unknown fact that the politically unstable, struggling with numerous economic, socio-ethnic problems, with a harsh climate, a huge North-East African country virtually unknown in Hungary, became a host country - even if for a short time - to a few Hungarians. However, two of the three Hungarian refugees – presumably - soon left Sudan, and the further fate of the lady who remained in Khartoum is still unknown to me. It can be stated that the chargé d’affaires of the Hungarian legation kept an eye on the Hungarians arriving in Sudan and as an aspiring young diplomat, respectively as a „good comrade”, he followed the instructions of the established Kádár-regimé in everything. For the preparation of my writing, apart from diplomatic sources, I was inspired by Gábor Búr’s lecture of 11 November 2021 on the arrival of Hungarian refugees in Africa in 1956.